REPRESENTASI MULTIKULTURALISME DALAM NOVEL MOBY DICK KARYA HERMAN MELVILLE - Ambar Andayani; Endang Purbowati (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2016)
ABSTRACT. This study expresses reflection of Herman Melville’s point of view about multiculturalism in his novel, Moby Dick (1851). Five indicators of characteristic of multicultural literature applied as the base of this study are: varied and unique characters, admission of equality of all characters, authentic character’s social background, values of ancient treasure, and author as part of story. By expressive-hermeneutic approach, it can be concluded as followings. First, Moby Dick represents varied and unique characters. Second, Moby Dick represents admission of equality of all characters. Third, Moby Dick shows authentic social background of characters. Fourth, Moby Dick promotes values of ancient treasure, namely tradition and religion (Christian). Fifth, Moby Dick represents Melville’s involvement as part of story through character (Ishmael). Therefore, Moby Dick really represents multicultural values.Keywords: represent, multiculturalism, exspressive-hermeneutic approach, multicultural literature